2023
DOI: 10.3390/plants12061323
|View full text |Cite
|
Sign up to set email alerts
|

The Leaf Essential Oil of Gynoxys buxifolia (Kunth) Cass. (Asteraceae): A Good Source of Furanoeremophilane and Bakkenolide A

Abstract: The present study describes the chemical and enantiomeric composition of a new essential oil, distilled from the dry leaves of Gynoxys buxifolia (Kunth) Cass. The chemical analysis was conducted by GC-MS and GC-FID, on two orthogonal capillary columns. A total of 72 compounds were detected and quantified with at least one column, corresponding to about 85% by weight of the whole oil mass. Of the 72 components, 70 were identified by comparing the respective linear retention indices and mass spectra with data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 85 publications
1
13
0
Order By: Relevance
“…As mentioned in the introduction, the EOs of other Gynoxys spp. from the same region (G. miniphylla, G. rugulosa, and G. buxifolia) have been described in previous studies, as a part of the present project [16][17][18]. On the one hand, the volatile fraction of G. buxifolia was very different from all the others, including the one described in the present report.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…As mentioned in the introduction, the EOs of other Gynoxys spp. from the same region (G. miniphylla, G. rugulosa, and G. buxifolia) have been described in previous studies, as a part of the present project [16][17][18]. On the one hand, the volatile fraction of G. buxifolia was very different from all the others, including the one described in the present report.…”
Section: Discussionsupporting
confidence: 52%
“…Despite being the less abundant of the major components (about 3%), this oxygenated sesquiterpene is absolutely the most interesting one, at least from the phytochemical point of view. In fact, whereas α-pinene, germacrene D, and (E)-β-caryophyllene are also the main components in almost all the EOs currently under investigation in the genus Gynoxys, bakkenolide A was only found so far in G. buxifolia [18]. On that occasion, the authors reported that the two main compounds (furanoeremofilane and bakkenolide A), despite being rare in EOs, are known to be often detected together in plants, due to biosynthetic reasons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ligustica 59.0 41.0 2.0 98.0 ------56.0 44.0 --------[43] .5 0.2 99.8 92.3 7.7 86.1 13.9 90.5 9.5 71.9 28.1 12.6 87.4 33.4 66.6 ----[15] Coreopsis triloba 18.4 81.6 100.0 0.0 2.5 97.5 --------0.6 ------71.6 28.4 --7.7 92.3 ----[50] .3 89.7 0.0 100.0 --------------[51] Gynoxys buxifolia 0.0 100.0 0.0 100.0 ------0.0 100.0 --------[52] Gynoxys miniphylla 0.9 99.1 44.1 55.9 ----------4.5 95.5 ----[53] Gynoxys rugulosa 37.1 62.9 100.0 0.0 ------57.4 42.6 49.9 50.1 95.5 4.5 ----[54] Solidago canadensis 73.9 26.1 36.4 63.6 97.7 2.3 --------72.4 27.6 ----[55] Tagetes maxima 88.3 11.7 57.6 42.4 95.6 4.4 --------------[56] …”
mentioning
confidence: 99%